PERAN TAKMIR MASJID DALAM MENGEMBANGKAN PENDIDIKAN AGAMA ISLAM DI MASJID BAITUR RAHMAN SIDOLUHUR LAWANG - Sofiatul Mukarromah; Khoirul Asfiyak; Zuhkhriyan Zakaria (VICRATINA, 2021)
The role of Takmir Masjid in developing islamic religious education at the Baitur Rohman mosque is by arranging various activites properly and ini an orderly manner, there is an arrangement of events for takmir to carry out mousque activities comfortably and well, as well the design og activities that the mosque takmir makes, namely the presence of majlis taklim for the whole community, recitation every week, recitation of sholawat nariyah once a week, tahlilan, albanjari practice, and also establishing Baitur Rohman foundations, namely Taman Pendidikan Al-qur’an (TPA) Baitur Rohman, Madrasah Diniyah (MADIN) Baitur Rohman, Ply Group Baitur Rohman. In developing islamic religious education, takmir does by arranging activities that can benefit ither people and the surrounding community, such as islamic studies activities, and also establishing learning places for children who are still in school, here takmir plays a very inportant role in the problem of continuing the activities that have been well structured. The results of this study (1) the role of the mosque in developing Islamic education at the Baitur Rahman Sidoluhur Lawang, (2) the role of the mosque in solving community problems, (3) the role of the mosque takmir in prospering Islamic education at the Baitur Rahman Sidoluhur Lawang